1997
DOI: 10.1002/etc.5620160226
|View full text |Cite
|
Sign up to set email alerts
|

Similarity analysis of PAH and PCB bioaccumulation patterns in sediment‐exposed Chironomus tentans larvae

Abstract: Larvae of the aquatic insect Chironomus tentans (Insecta: Diptera: Chironomidae) were exposed at the third or fourth instar stage to sediments collected near the outfalls of two aluminum foundries and an aluminum fabrication plant. Biota and sediment bioaccumulation factors (BFs), based on wet tissue weights and dry sediment weights, ranged from 0.07 to 0.27 for polycyclic aromatic hydrocarbons (PAHs) and from 0.22 to 1.42 for polychlorinated biphenyls (PCBs). A higher rate of metabolism of PAHs compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Also, the abundance of octachlorinated congeners in relation to other congeners in tissue samples also resulted in nonlinearity in trends for oligochaetes (Figures 2 and 4). Wood et al (34) observed a similar increase in tendency for bioaccumulation along increasing chlorination degree for PCBs in Chironomus tentans. It was explained by the increasing relative contribution of intestine (sediment) as compared to integument (pore water) as an accumulation route along increasing lipophilicity of contaminant.…”
Section: Impact Of Contaminant Steric and Electrochemical Characterismentioning
confidence: 72%
“…Also, the abundance of octachlorinated congeners in relation to other congeners in tissue samples also resulted in nonlinearity in trends for oligochaetes (Figures 2 and 4). Wood et al (34) observed a similar increase in tendency for bioaccumulation along increasing chlorination degree for PCBs in Chironomus tentans. It was explained by the increasing relative contribution of intestine (sediment) as compared to integument (pore water) as an accumulation route along increasing lipophilicity of contaminant.…”
Section: Impact Of Contaminant Steric and Electrochemical Characterismentioning
confidence: 72%
“…It is well documented that Ž HOCs accumulate in sediments Kennicutt et al, 1993; . Zeng and Vista, 1997 , can cause adverse effects on Ž benthic organisms Knezovich et al, 1987;Wood et al, . 1997 , bioconcentrate in aquatic organism tissues Ž .…”
Section: Us Environmental Protection Agency Assessment Technique Fomentioning
confidence: 99%